Ecoeconomy and sustainable development as principal concepts of a serious proposal for Perú - Córdova, Jesús H. (2001)
The forcefulness of the facts has shown an unquestionable truth: the life on Earth is sustained by a limited quantity of energy that is produced by organisms like the green plants. It is urgent to put into practice measures that assure the maintenance of at least such a quantity of energy. The growing deforestation rate and contamination (pollution), as by-products of the “modernity”, allows us to watch the seriously committed humanity’s future, not being necessary to wait to the generation of our children to appreciate their negative effects. In the beginning of the XXI century we already live them and inclusive we can even quantify them. It will be necessary to decide what to make in order to avoid one of the biggest ecological disasters: the asphyxia of the planet. The only formulas that can to avoid this outcome lie within the concept of Eco-Development or Sustainable Development, inspiring in the most revolutionary ideas in State philosophy—Eco-Economy. Here we offer some fundamental precepts on which Ecoeconomy is based, and we point out the dangers of not acting quickly enough according to their advice in countries that possess an enormous magnitude of biological diversity as the Peru (which is one of the top ten recognized worldwide). For Sustainable Development purposes, being megadiverse condition in a world of globalized markets amounts to an enormous strength, that can generate —provided there is a political will— an inexhaustible source of potentialities and opportunities, which could enable the country to reach significant and growing levels of benefits in the short, medium and long term.